2002
DOI: 10.1111/j.1530-0277.2002.tb02647.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐Induced Up‐Regulation of Fibrinolytic Activity and Plasminogen Activators in Human Monocytes

Abstract: These data suggest that low alcohol exerts a rapid, direct, and sustained effect on monocyte fibrinolytic activity, which may be, due in part, to increased monocyte t-PA/u-PA expression. These data provide a feasible molecular mechanism by which alcohol effects on monocyte fibrinolysis may contribute to the cardioprotective benefit associated with moderate alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…tPA activity was also induced in the meninges ( Fig. 1 d and e), which is consistent with its up-regulation in nonneuronal cells by ethanol (28,29).…”
Section: Results Tpa Is Up-regulated By Ethanol and Ewsupporting
confidence: 83%
“…tPA activity was also induced in the meninges ( Fig. 1 d and e), which is consistent with its up-regulation in nonneuronal cells by ethanol (28,29).…”
Section: Results Tpa Is Up-regulated By Ethanol and Ewsupporting
confidence: 83%
“…1 Moderate alcohol increases clot lysis in vivo in a mouse model, by increasing the expression of tissue plasminogen activator (t-PA) and urokinase plasminogen activator (u-PA), 8 a response also detected in human monocytes. 9 In contrast to the effect of alcohol, a deficit in eNOS function raises plasma fibrinogen. 10,11 It has been shown that eNOS plays a key role in the process of thrombosis.…”
Section: Haemostatic Mechanismsmentioning
confidence: 98%
“…The exact mechanisms by which excessive alcohol consumption decrease serum levels of the 7.8 kDa fragment of apo-AII and the 5.9 kDa fragment of ␣E chain of fibrinogen remain to be investigated. It is of note that alcohol-induced alteration of fibrinolytic activity has been shown in human monocytes [33].…”
Section: Surface Enhanced Laser Desorption/ionization Time-of-flight mentioning
confidence: 99%